Characterization of a MEMS-Based Humidity Sensor - AMIN ALI, AHMED ABDELAZIZ (Universiti Teknologi PETRONAS, 2017)
Humidity sensors are very essential in many industrial processes and household appliances. They enable system operators and control mangers to fully monitor their processes in the industry. However, these sensors are miniaturized to be in micro-scale units due the development of micromachining technology. As a consequence, the sizes and the performance of the sensors have been drastically improved to be compatible with various complex systems. Whereas, the cost of the sensors have become much lower. Such devices are called Micro-Electro-Mechanical Systems (MEMS). There are many types of MEMS-Based humidity sensors such as capacitive humidity sensor and Piezoresistive humidity sensor. This research work describes the performance of a capacitive MEMS-Based humidity sensor that is fabricated using PolyMUMPS process which is a three-layer surface micromachining process. Therefore, the key purpose of this project is to mechanically and electrically characterize a MEMS-Based capacitive humidity sensor that it is actuated using electromagnetic actuation method based on Lorentz force principle. The designed integrated sensor encompasses of a sensing element and a capacitive readout circuit.